Analisis Biaya dan Waktu pada Proyek Jembatan (Studi Kasus Proyek Pembangunan Jembatan Candisari Sambeng Kabupaten Lamongan) dengan Menggunakan Metode Earned Value - Jazuli, M.; Dhana, Rio Rahma (Universitas Batanghari Jambi, 2024)
Project management has three main objectives when carrying out construction projects including cost, quality, and time. If a project can be completed with a predetermined level of quality or quality, then the project has been successfully managed. This research uses earned value method. That is a method of knowing costs based on the work that has been done. Thus we can find out whether the Candisari Sambeng bridge construction project in Lamongan Regency is faster or longer than the schedule that has been made. CV value has a negative value in the 15th period, namely -Rp 18,078,304 SV value there is a negative value until the 18th period with a value of -Rp 494,817,905 CPI value found in the 15th week period with a value of 0.995. The SPI value in the 18th period with a final SPI value of 0.903 estimated cost (EAC) is. IDR 5,166,992,802 estimated EAS time for the jembata replacement project of 21,320 weeks. If the performance is considered the same project, the cost required to complete the construction of the bridge is Rp 5,166,992,802 from the total project budget of Rp 5,346,534,000 so that it gets a profit of Rp 179,541,198, and the time needed to complete the construction work is 21,320 weeks from the specified time of 21 weeks so that the project implementation is delayed for 0,320 weeks.y.